Paraquat-induced neurogenesis abnormalities via Drp1-mediated mitochondrial fission - Bing Zhang; Yuwei Zhang; Zhenzi Zuo; Guiya Xiong; Huan Luo; Bo Song; Lina Zhao; Zhijun Zhou; Xiuli Chang (Ecotoxicology and Environmental Safety, 2023)
Neurogenesis is a fundamental process in the development and plasticity of the nervous system, and its regulation is tightly linked to mitochondrial dynamics. Imbalanced mitochondrial dynamics can result in oxidative stress, which has been implicated in various neurological disorders. Paraquat (PQ), a commonly used agricultural chemical known to be neurotoxic, induces oxidative stress that can lead to mitochondrial fragmentation. In this study, we investigated the effects of PQ on neurogenesis in primary murine neural progenitor cells (mNPCs) isolated from neonatal C57BL/6 mice. We treated the mNPCs with 0–40 μM PQ for 24 h and observed that PQ inhibited their proliferation, migration, and differentiation into neurons in a concentration-dependent manner. Moreover, PQ induced excessive mitochondrial fragmentation and upregulated the expression of Drp-1, p-Drp1, and Fis-1, while downregulating the expression of Mfn2 and Opa1. To confirm our findings, we used Mdivi-1, an inhibitor of mitochondrial fission, which reversed the adverse effects of PQ on neurogenesis, particularly differentiation into neurons and migration of mNPCs. Additionally, we found that Mito-TEMPO, a mitochondria-targeted antioxidant, ameliorated excessive mitochondrial fragmentation caused by PQ. Our study suggests that PQ exposure impairs neurogenesis by inducing excessive mitochondrial fission and abnormal mitochondrial fragmentation via oxidative stress. These findings identify mitochondrial fission as a potential therapeutic target for PQ-induced neurotoxicity. Further research is needed to elucidate the underlying mechanisms of mitochondrial dynamics and neurogenesis in the context of oxidative stress-induced neurological disorders.